Hubungan Pengetahuan Ibu tentang Pola Pemberian Makanan Pendamping ASI Dengan Status Gizi Bayi Usia 6-24 Bulan di Wilayah Puskesmas Kedawung Kecamatan Kedawung Kabupaten Cirebon - Sofiyati Sofiyati (Universitas Malahayati Lampung, 2022)
ABSTRACT: THE RELATIONSHIP OF MOTHER'S KNOWLEDGE ABOUT THE PATTERN OF COMPLEMENTARY FEEDING OF BREASTFEEDING (MPASI) WITH NUTRITIONAL STATUS OF INFANTS AGED 6-24 MONTHS IN THE AREA OF KEDAWUNG PUSKESMAS, KADAWUNG REGENCY, CIREBON REGENCY Introduction: Malnutrition is one of the problems in infants and children that can lead to impaired growth and development. Infants aged 6-24 months are not enough just to give breast milk alone, but the presence of complementary foods (MPASI).Objective: To determine the relationship between a mother's knowledge about how to give food can cause babies to be malnourished.Research Methods: The subjects in this study were infants aged 6-24 months at the Kedawung Health Center, Kedawung District, Cirebon Regency. Respondents are mothers who have babies aged 6-24 months as many as 27 people. This type of research is observational with a cross-sectional approach, the method is through interviews using questionnaires with data collection techniques using simple random sampling and weight measurement using digital scales. The data analysis technique used the Chi-Square test with a significant level of 0.05 on SPSS 16.0 for windows.Results: The results showed that most of the mothers had knowledge about complementary feeding patterns as many as 12 people (44%), good category 7 people (26%). However, there are still 8 (30%) mothers who have less knowledge and there is a significant relationship between mothers' knowledge about the pattern of giving complementary foods to breast milk and the nutritional status of infants aged 6-24 months. This is indicated by the value of p = 0.062 0.05.Conclusion: Suggestions in this study are the need to increase mother's knowledge, especially about nutrition related to complementary feeding of breast milk in her baby, immediately take care as soon as possible in infants with poor nutritional status, and the role of health services in handling it. . Malnutrition is very necessary for the continuity of infant growth and development, including through counseling, discussions and other activities by nutrition officers and posyandu cadres in the Kedawung Health Center area, so that good eating patterns and complementary breastfeeding can be implemented in an effort to improve nutritional status. Keywords: mother's knowledge, nutritional status INTISARI: HUBUNGAN PENGETAHUAN IBU TENTANG POLA PEMBERIAN MAKANAN PENDAMPING ASI DENGAN STATUS GIZI BAYI USIA 6-24 BULAN DI WILAYAH PUSKESMAS KEDAWUNG KECAMATAN KEDAWUNG KABUPATEN CIREBON Pendahuluan: Kekurangan gizi merupakan salah satu masalah pada bayi dan anak, yang dapat mengakibatkan terganggunya pertumbuhan dan perkembangannya. Bayi usia 6-24 bulan tidak cukup hanya dengan pemberian ASI saja melainkan adanya makanan pendamping ASI (MPASI).Tujuan: untuk mengetahui hubungan pengetahuan ibu tentang cara pemberian makanan dapat menyebabkan bayi tidak terpenuhi gizinya.Metode Penilitan: Subjek pada penelitian ini adalah bayi dengan usia 6-24 bulan di wilayah Puskesmas Kedawung Kecamatan kedawung Kabupaten Cirebon. Adapun respondennya adalah ibu yang memiliki bayi usia 6-24 bulan sebanyak 27 orang. Jenis penelitian ini adalah observasional dengan pendekatan cross sectional, Metode melalui wawancara menggunakan kuesioner dengan teknik pengambilan datanya menggunakan simple random sampling serta pengukuran berat badan menggunakan timbangan digital. Teknik analisis data menggunakan uji Chi Square dengan taraf signifikan 0,05 pada SPSS 16.0 for windows.Hasil: Hasil penelitian menunjukkan bahwa sebagian besar ibu memiliki pengetahuan tentang pola pemberian makanan pendamping ASI dengan kategori cukup sebanyak 12 orang (44%), kategori baik sebanyak 7 orang (26%). Namun masih ada 8 orang (30%) ibu yang memiliki pengetahuan kurang serta terdapat hubungan yang signifikan antara pengetahuan ibu tentang pola pemberian makanan pendamping ASI dengan status gizi bayi usia 6-24 bulan. Hal ini di tunjukkan dengan nilai p= 0,062 0,05.Kesimpulan: Saran dalam penelitan ini perlunya peningkatan pengetahuan ibu terutama tentang gizi yang bekaitan dengan pemberian MPASI bagi bayinya, segera dilakukan penanganan sesegera mungkin untuk bayi dengan status gizi buruk serta peran pelayanan kesehatan dalam menangani kasus gizi buruk sangat diperlukan untuk kelangsungan tumbuh kembang dari bayi, antara lain melalui penyuluhan, diskusi serta kegiatan lainnya oleh petugas gizi dan para kader posyandu di wilayah Puskesmas Kedawung, agar dapat diimplementasikannya pola makan dan pemberian MPASI yang baik bagi bayinya dalam upaya peningkatan status gizi. Kata kunci: pengetahuan ibu, status gizi